Physical Damages of Wood Fiber in Acacia Mangium due to Biopulping Treatment - Ridwan Yahya; Mucharromah Mucharromah; Devi Silsia; Septiana Septiana (Molekul, 2016)
Biopulping is fungal pretreatment of wood chips to reduce unused chemical composition of material in pulping. Preliminary study showed that pretreatment of Phanerochaetachrysosporium to Acacia mangium Willd can reduce lignin and improve holocellulose and cellulose content of the material. Fiber dimension recognized as other important factor for paper properties. The question is how the integrity and dimensions of the wood fiber that has been pretreated with the fungus. The objectives of present study were to know effect of pretreatment of P. chrysosporium to the integrity and dimensions of the fiber. The P. chrysosporium was cultured for 14 days in growth medium, and inoculated to wood chips 5% (w/v) and incubated for 0, 15 and 30 days. The inoculated wood chips were chipped into 1 mm x 1 mm x 20 mm and macerated using franklin solution at 60 oC for 48 hours. Forty fibers from each incubated time were analized their physical damages using a light microscope at a 400 magnification. The inoculated fibers were measured theirs dimensions. The physical damage percentage of fibers pretreated using P. chrysosporium was 0%. Length and wall thickness of the pretreated fibers were can be categorized as middle class and thin fibers, respectively.